2022
DOI: 10.1021/acs.joc.1c03160
|View full text |Cite
|
Sign up to set email alerts
|

Access to Diarylmethanols by Wittig Rearrangement of ortho-, meta-, and para-Benzyloxy-N-Butylbenzamides

Abstract: The N -butyl amide group, CONHBu, has been found to be an effective promoter of the [1,2]-Wittig rearrangement of aryl benzyl ethers and thus allow the two-step synthesis of isomerically pure substituted diarylmethanols starting from simple hydroxybenzoic acid derivatives. The method is compatible with a wide range of functional groups including methyl, methoxy, and fluoro, although not with nitro and, unexpectedly, is applicable to meta as well as orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The authors have cited additional references within the Supporting Information. [59][60][61][62][63][64][65]…”
Section: Discussionmentioning
confidence: 99%
“…The authors have cited additional references within the Supporting Information. [59][60][61][62][63][64][65]…”
Section: Discussionmentioning
confidence: 99%
“…62 Finally the n-butyl amide group was found to promote the rearrangement in moderate to high yield and was effective in ortho-, meta-, and para-positions giving diarylmethanol products 70. 63 This method has since been extended to the phosphonamide directing group giving 71, 64 and further studies on oxazoline-based systems have also been reported. 65 Arising from a fundamental study on FVP of a-functionalised carboxylic acid derivatives, dioxolanones derived from lactic or mandelic acid were found to be effective chiral acyl anion equivalents.…”
Section: O Phmentioning
confidence: 99%
“…More recently, we discovered the N-butylcarboxamide CONHBu as a more efficient and general activating group, allowing the Wittig rearrangement of ortho-, meta-, or paraoriented benzylic ethers 5 to afford diarylmethanols 6 [6]. A limited degree of success in using a chiral secondary amide group to bring about asymmetric Wittig rearrangement was also described [7].…”
Section: Introductionmentioning
confidence: 99%
“…Organics 2024, 5, FOR PEER REVIEW 2 Scheme 1. General strategy for indirect C-C bond formation via ether formation and Wittig rearrangement and previously reported examples [4,6].…”
Section: Introductionmentioning
confidence: 99%